Young adults’ satisfaction towards hipster cafes: the brewing factors / Asyraf Sharee and Nur Shahrulliza Muhammad - Sharee, Asyraf; Muhammad, Nur Shahrulliza (2018)
The ever changing preference and taste in food service industry due to increase in demand causes the market to become competitive in Malaysia. With the emergence of hipster cafes in Malaysia’s coffee scene, hipster cafe operators are strategically expanding their wings to capture the market share in order to gain competitive advantage over the competitors. Customers will prefer a hipster cafe which is able to provide better quality of offerings and customer services. This study tested the influence of factors of Food Quality, Service Quality and Restaurant Environment on Customer Satisfaction. Findings are derived from 150 digital questionnaires administered using emails and iPads at a number of hipster cafes in Klang Valley. Evidently, Restaurant Environment triumphed as the brewing factor that draws the young adults to dine in the hipster cafes.